The nature and controls on downstream change of channel sediment along the Shiyang River, Northwest China - Li, Ping; Gao, Hongshan; Yan, Tianqi; Li, Zongmeng; Wu, Yajie; Liu, Fenliang (Frontiers in Earth Science, 2023)
The grain size composition and distribution of river sediments are important for understanding regional geomorphological evolution, source-sink processes and drainage ecology. The Shiyang River basin, an inland river system in northwestern China, provides an environmental context within which to investigate the relationship between sediment particle size and environmental factors. Based on the analysis of the grain size characteristics of modern riverbed sediments, basin geomorphological parameters and lithology, it is found that the median grain size (Md) of river sediments shows a decrease trend from upstream to downstream in the basin. One of the tributaries named the Jinta River shows an obvious downstream fining trend (exponentially decreasing) of Md, which is related to the old geomorphological development stages and relatively homogeneous lithology in the basin. The downstream fining trend of Md along the Xiying River, another tributary, shows complex fluctuations, which might be affected by the tectonically active, young geomorphic development stage, complex lithology of the basin, and the sediment confluence of tributaries. The gravel-sand transition zone occurs in the plain section of the river about 28 km out of the mountain, which is related to the combination of regional geomorphological features, river morphology and hydraulic sorting.